Compensating Differentials and Self-Selection: An Application to Lawyers - Goddeeris, John H. (Journal of Political Economy, 1988)
This paper models individual choice between two types of jobs as dependent on the difference in potential earnings and on preferences for nonpecuniary The model leads to simultaneous estimation of earnings and job choice functions in a manner that takes account of self-selection of individuals into the sector of highest utility. An application to lawyers choosing between private and "public-interest" law casts doubt on the notion that public-interest lawyers are accepting substantially lower earnings by virtue of their choice–an impression derived from estimation of earnings functions without accounting for self-selection. The estimation technique also takes proper account of the "choice-based" nature of the sample, which appears to be important.